Integrating Fiqh, Maqasid Sharīa, and ESG: A Proposed Framework for Risk Management in Islamic Banking - Sandy Rizki Febriadi Sanusi; Zaini Abdul Malik; Ifa Hanifia Senjiati; Fitri Yuniawati (Sekolah Tinggi Agama islam Negeri Majene, 2026)
Islamic banks are undergoing rapid digital transformation, yet this shift brings new vulnerabilities and increases exposure to climate‑related risks. These challenges indicate that digitalisation is not merely a technological upgrade but a strategic evolution requiring Islamic banks to embed sustainability and resilience at the core of their governance systems. This study aims to explain the integration of Fiqh principles and Maqāṣid Sharīa in Islamic bank risk management and explore the relevance of ESG to risk management. It also seeks to develop an ESG framework aligned with Fiqh and Maqāṣid Sharīa. Using a qualitative descriptive case study approach, this research examines Bank Syariah Indonesia (BSI) as the primary unit of analysis. Data were collected through triangulation (semi‑structured interviews with Sharia authorities and practitioners), document analysis of BSI’s 2023–2024 Sustainability Reports, relevant regulations, and direct observation of ESG implementation. The findings reveal that Fiqh provides the legal foundation for risk governance, while Maqāṣid Sharīa functions as an ethical and teleological compass guiding decision‑making toward public welfare. ESG, in turn, offers operational tools that transform Sharia values into measurable sustainability practices. Evidence from BSI’s initiatives in sustainable financing and digital financial inclusion demonstrates that ESG can operate as a vital instrument for risk mitigation while simultaneously generating positive socio‑environmental impact. Key implications include the need for regulators to develop ESG reporting standards that are integrated with Islamic law, the importance of capacity building for Sharia Supervisory Boards and risk management teams, and the necessity of industry‑wide commitment to sustainability as a driver of long‑term competitiveness and institutional resilience.